The Advantages of Polymer Composites with Detonation Nanodiamond Particles for Medical Applications - Pramatarova, L.; Radeva, E.; Pecheva, E.; Hikov, T.; Krasteva, N.; Dimitrova, R.; Mitev, D.; Montgomery, P.; Sammons, R.; Altankov, G. (IntechOpen, 2011)
None